The Art of Redirection: One Library's Experiences and Statistical Results From the Deployment of Mobile Redirect Script - Bengtson, Jason A. (My University, 2012)
Although institutions have produced a proliferation of mobile Web sites to respond to the increased demand for mobile resources, getting mobile device users to those sites has proven to be an issue. One simple method involves the use of script that automatically redirects mobile devices from an institution's regular Web site to a mobile site. This article documents the experience of the University of New Mexico's Health Sciences Library and Informatics Center with its mobile redirect strategy. The strategy is presented here in its evolving entirety, along with statistics of Web site usage to evaluate the success of the effort.
Citation: Bengtson, Jason. "The Art of Redirection: One Library's Experiences and Statistical Results from the Deployment of Mobile Redirect Script." Journal of Hospital Librarianship 12.3 (2012) : 191-198. Print
Keywords: IT; Mobile; Smart Phone; Tablet Web App; Web Site Design; World Wide Web